THE EFFECTIVENESS OF ELECTRONIC AUDITING IN REDUCING FINANCIAL AND ADMINISTRATIVE VIOLATIONS IN GOVERNMENT INSTITUTIONS - Amel Merzah Sakhil Alkuzaly; Yas Khudhair Abbas; Shaymaa Nihro Jabal Afloogee (Journal Park Publishing, 2024)
This study aimed to show the effectiveness of electronic auditing in reducing financial and administrative violations in government institutions, a questionnaire was built consisting of (54) paragraph, and (130) questionnaire was distributed to a sample of audit units in the Audit and Control Bureau and financial managers and accountants in commercial banks in Baghdad Governorate, which numbered (12) Bank and company, as (112) questionnaire was obtained, Equivalent to (86%), the study adopted the descriptive analysis approach in measuring its variables, and The findings indicated that electronic auditing of implementation is required to lower the rate of fraud and administrative and financial corruption, as well as to improve the quality of service delivery for improved performance, As well as the existence of a positive relationship between the use of electronic audit and the reduction of financial and administrative violations, this improves the ability of banks to analyze financial and administrative data more accurately and effectively, which enables financial controllers and auditors to detect irregularities faster and more effectively. This helps to reduce the volume of financial and administrative irregularities and improve financial and administrative management in organizations.
Keywords: electronic audit, financial and administrative violations, government institutions.